Features of Fortifications of the Tsaritsyn Defense Line in the 20s of the 18th Century - Sergey Ivanyuk (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2021)
Introduction. Extending from the walls of the fortress of Tsaritsyn to the Don river, the Tsaritsyn defense line reliably protected this area from the systematic raids of nomads, gave an impetus to the active settlement of the region and its economic development. A number of research papers are devoted to the history of the Tsaritsyn line, but some aspects are still insufficiently studied. This article reveals the features of fortification and military engineering characteristics of the Tsaritsyn defense line defensive structures, its technical condition during the reign of Peter I. Methods and materials. The research is based on both published documents and ones stored in archives, which allow us to understand the principles that formed the fortified Tsaritsyn defense line, which fortifications were part of its complex in the 20s of the 18th century. Methods of the study: the principles of historicism and objectivity, analysis, synthesis, systematic approach. Analysis. The comparison of the evidence of participants in the construction of the Tsaritsyn defense line (1719–1720) and cartographic plans of its fortifications made it possible to determine the main characteristics of military engineering facilities located at it. Additionally, the analysis of cartographic sources, the manuscript division of the Library of the Academy of Sciences and the documents of the Main Office of Artillery and Fortification helped to determine the time frame and the author of the map “of the defensive line between the Volga and the Don” of 1723, which has not previously been used by researchers when working on the issue of fortification of the Tsaritsyn defense line in the first years of its operation. Results. As a result of the conducted research, it was found that since the beginning of commissioning in 1720, the main fortification objects were formed at the Tsaritsyn defense line, which were part of the complex of its defensive structures, which remained the main fortifications during the entire time of its operation until the abolition of service on it.